The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevb.78.033202
|View full text |Cite
|
Sign up to set email alerts
|

Divacancy clustering in neutron-irradiated and annealedn-type germanium

Abstract: We have studied the annealing of vacancy defects in neutron-irradiated germanium. After irradiation, the Sb-doped samples ͓͑Sb͒ = 1.5ϫ 10 15 cm −3 ͔ were annealed at 473, 673, and 773 K for 30 min. The positron lifetime was measured as a function of temperature ͑30-295 K͒. A lifetime component of 330 ps with no temperature dependence is observed in as-irradiated samples, identified as the positron lifetime in a neutral divacancy and indicating that the divacancy is stable at room temperature ͑RT͒. Annealing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
7
23
0
Order By: Relevance
“…Furthermore, strong evidence of a negative charge state for the divacancy in the bandgap was also reported. 28 These findings are supported by a recent DLTS study by Petersen et al 29 A few low-temperature irradiation PAS studies on germanium have previously been reported. [30][31][32] A common feature of all these studies is that electron irradiation has been performed at cryogenic temperatures, and the samples have then been transported and measured at liquid nitrogen temperatures.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, strong evidence of a negative charge state for the divacancy in the bandgap was also reported. 28 These findings are supported by a recent DLTS study by Petersen et al 29 A few low-temperature irradiation PAS studies on germanium have previously been reported. [30][31][32] A common feature of all these studies is that electron irradiation has been performed at cryogenic temperatures, and the samples have then been transported and measured at liquid nitrogen temperatures.…”
Section: Introductionsupporting
confidence: 72%
“…28. As the average lifetime at RT in the sample used in this study is considerably lower as compared with that of Ref.…”
Section: Discussionmentioning
confidence: 58%
“…There are very few quantitative PAS studies done in germanium and to make a more exact estimate of the cluster size is therefore difficult. However, a qualitative estimate can be made by using the present results in conjunction with the recent result for the Ge divacancy 15 and by comparing with similar studies in silicon. 10 Hakala et al found an approximately linear relation between the normalized S parameter and the cluster size.…”
Section: B Pasmentioning
confidence: 82%
“…Fewer results were published concerning highpurity germanium detectors for which early efforts were significant. Published results seems to show that annealing is not complete, although radiation induced point defects anneal out around 200°C (Mooney et al,1983; , clusters and other extended defects remain in the bulk of the crystal and only disappear at higher temperatures (Kuitunen et al,2008). Other materials are used for semiconductor detectors, but have not attracted so much interest in terms of radiation tolerance.…”
Section: Ionizing Irradiation Issues 311 Semiconductor Detectors (Nmentioning
confidence: 99%